Pendampingan Implementasi Penggunaan QRIS Pada Penerimaan Infaq di Masjid Jami’ Nurul Ihsan - Harahap, Cece (Sekolah Tinggi Ilmu Manajemen Sukma Medan, 2024)
The digitalization of mosque financial governance has become a crucial necessity in the cashless economy era to enhance transparency and efficiency in collecting community funds. The primary issue faced by Jami’ Nurul Ihsan Mosque was the conventional management of alms, which posed risks to fund security and limited access for congregants who did not carry cash. The purpose of this community service activity is to assist in the implementation of the Quick Response Code Indonesian Standard (QRIS) as a digital solution for receiving alms. The method used is qualitative research with a case study approach, encompassing stages of observation, account registration with payment service providers, technical training for administrators, and socialization to the congregation. The results of the assistance show an increase in the digital literacy of mosque administrators and the creation of an automated and accountable financial recording system. Furthermore, the placement of QRIS media in strategic locations has facilitated congregants in distributing alms through various digital wallet applications. In conclusion, the implementation of QRIS is proven effective in increasing the flexibility and security of mosque financial management and strengthening congregational trust. The recommendation from this activity is the need for continuous education from the mosque committee to the congregation and the periodic utilization of digital reporting features to maintain consistent financial transparency. The success of this mentoring model is expected to serve as a reference for other mosques in adopting financial technology for the economic independence of the community.